Coffee Processed Product Innovation in Kampung Pelita Bondowoso - Dina Tsalist Wildana; Laili Furqoni (LP2M Universitas Jember, 2019)
Bondowoso has been known as a city of tape. This district also has the potential of coffee plantations that have produced products until it is known as the Republic of Coffee. The purpose of this activity is to increase public knowledge about various kinds of processed coffee, provide value added products, and attract consumers to come to visit the region. The method used is trial and error and utilizes the University of Jember Real Lecture Program where the target area is Sub-District Tamansari, Bondowoso District, Bondowoso Regency. The results of the activities include the emergence of innovations in processed coffee products such as: coffee dawet, coffee marrow porridge, Cilok Kopi, coffee fried rice and coffee ladrang. This activity was supported by PKK ladies and received support from Blue Gas. Such innovation activities are quite interesting for the community because they are able to make various kinds of processed foods from coffee. It's just that more intensive training is needed so that these processed products can support Bondowoso tourism.